Aspects of Reading - Markovic, Desa (Murmurations: Journal of Transformative Systemic Practice, 2021)
Abstract As a tutor and a teacher on various psychotherapy and supervision courses over time, I became aware of the need for a structured framework that would guide discussions on the literature during the sessions with students. The feedback from tutors and students has encouraged me to continue to use it and particularly emphasised its potential to stimulate self-reflexive thinking. The Model is presented as a format for reading papers, discussing the material with others, and giving an account of reading such as writing a critique or a literature review. The purpose of the ‘Aspects of Reading’ is to enhance possibilities for learning by highlighting different positions a reader can take during these activities. Abstract As a tutor and a teacher on various psychotherapy and supervision courses over time, I became aware of the need for a structured framework that would guide discussions on the literature during the sessions with students. The feedback from tutors and students has encouraged me to continue to use it and particularly emphasised its potential to stimulate self-reflexive thinking. The Model is presented as a format for reading papers, discussing the material with others, and giving an account of reading such as writing a critique or a literature review. The purpose of the ‘Aspects of Reading’ is to enhance possibilities for learning by highlighting different positions a reader can take during these activities.